Dynamic structural response monitoring of tall buildings using GPS - Brownjohn, James Mark William (2008)
This report presents research carried out up to December 2004 aimed at tracking the dynamic, static and quasi-static movements of a tall building under the influence of wind, earthquakes and thermal effect, using conventional instrumentation and a system designed to use the global positioning system (GPS) to identify absolute displacements. The is an extension of an earlier program (RP11/93) that begin to look at lateral loading of tall buildings in Singapore due to wind and earthquake effects. At the end of that program, the static and dynamic performance of Republic Plaza had been completely mapped from readings of static instrumentation installed by the contractor, ad-hoc measurements using a pair of accelerometers and an ambient vibration survey performed using final year project students. Between the end of that project and the start of this one, a wind and acceleration monitoring system has been installed and operated, while an extensive finite element model updating exercise has been used to derive an accurate model of the building.